Komparasi Posisi Pasar antara Indonesia dan Malaysia pada Pasar Refined Palm Oil (RPO) Amerika Serikat - Risnayanti Ulfa Aulia; . Harianto; Tanti Novianti (Jurnal Ilmu Pertanian Indonesia, 2019)
United States is one of the major importer countries of Refined Palm Oil (RPO) and its imports increase about 21.25%/year because of a high domestic consumption. The main sources of US RPO’s import are Malaysia and Indonesia with shares of 70.21 and 27.29% respectively. The purposes of this research are to 1) Estimate the factors affecting RPO’s import in the United States and 2) Analyze themarket position and competition between Indonesia and Malaysia in the RPO market in the United States. The methods used were linear regression using Ordinary Least Square (OLS) and Almost Ideal Demand System (AIDS) model. Factors affecting RPO import in US market are the import price of RPO and RSO, GDP, and dummy Non-Tariff Measures (NTM). In US market, teh RPO from Indonesia and Malaysia are substitute each other and Indonesia’s RPO are more sensitive (elastic) to prices and expenditure compared to Malaysia’s RPO in the US market.